Rapamycin Inhibited Pyroptosis and Reduced the Release of IL-1β and IL-18 in the Septic Response. (10th August 2020) - Zhuo, Luo; Chen, Xiaobing; Sun, Yan; Wang, Yanli; Shi, Yuanfeng; Bu, Lin; Xia, Wei; Han, Jiayan; Chen, Dongmei; Li, Xiaomin
Abstract : Pyroptosis, an inflammatory form of programmed cell death, is the initiating event of sepsis and results in immune imbalance by releasing IL-1 β and IL-18 in the early stages. Studies show that enhancing autophagy via genetic manipulation can inhibit pyroptosis and prolong the survival of a sepsis animal model, indicating a possible therapeutic strategy against sepsis. However, almost no study so far has achieved pyroptosis inhibition via pharmacological autophagy induction in a sepsis disease model. To this end, we established an in vitro sepsis model by stimulating primary human umbilical vein endothelial cells (HUVECs) with lipopolysaccharide (LPS), and analyzed the effect of the autophagy agonist rapamycin (RAPA) on pyroptosis. Phorbol 12-myristate 13-acetate- (PMA-) activated human THP-1 cells were used as the positive control. LPS significantly increased the levels of the pyroptotic protein Gasdermin D (GSDMD), cysteinyl aspartate-specific proteinase 1 (caspase-1), secreted LDH, IL-1 β, and IL-18. RAPA treatment downregulated the above factors and enhanced autophagy in the LPS-stimulated HUVECs and THP-1 cells. This study shows that RAPA abrogates LPS-mediated increase in IL-1 β and IL-18 by inhibiting pyroptosis and enhancing autophagy.